Characteristics and result reporting of registered COVID-19 clinical trials of Chinese and Indian traditional medicine: A comparative analysis - Zhao, Nan; Pandey, Kritika; Lakshmanan, Skanthesh; Zhao, Ran; Fan, Jingchun; Zhang, Junhua; Bachmann, Max O.; Fan, Hong; Song, Fujian (Frontiers in Medicine, 2023)
Objective To assess the main characteristics and result reporting of registered COVID-19 interventional trials of traditional Chinese medicine and traditional Indian medicine. Materials and methods We assessed design quality and result reporting of COVID-19 trials of traditional Chinese medicine (TCM) and traditional Indian medicine (TIM) registered before 10 February 2021, respectively, on Chinese Clinical Trial Registry (ChiCTR) and Clinical Trial Registry-India (CTRI). Comparison groups included registered COVID-19 trials of conventional medicine conducted in China (WMC), India (WMI), and in other countries (WMO). Cox regression analysis was used to assess the association between time from trial onset to result reporting and trial characteristics. Results The proportion of COVID-19 trials investigating traditional medicine was 33.7% (130/386) among trials registered on ChiCTR, and 58.6% (266/454) on CTRI. Planned sample sizes were mostly small in all COVID-19 trials (median 100, IQR: 50–200). The proportion of trials that were randomized was 75.4 and 64.8%, respectively, for the TCM and TIM trials. Blinding measures were used in 6.2% of the TCM trials, and 23.6% of the TIM trials. Cox regression analysis revealed that planned COVID-19 clinical trials of traditional medicine were less likely to have results reported than trials of conventional medicine (hazard ratio 0.713, 95% confidence interval: 0.541–0.939; p = 0.0162). Conclusion There were considerable between-country and within-country differences in design quality, target sample size, trial participants, and reporting of trial results. Registered COVID-19 clinical trials of traditional medicine were less likely to report results than trials of conventional medicine.